Management of dynamic and adaptive workflow business processes - Pudhota, Leo; Chang, Elizabeth (CSREA Press, 2006)
Collaborative and dynamic workflow management systems in logistic companies require strong information systems and computer support. Business processes in such industries generally compose of several parts, a structured operational part and an unstructured operational part, or they could be composed of semistructured parts with some given and some unknown details. Unpredictable situations may occur as a result of changes in decisions made by the management. The inability to deal with various changes greatly limits the applicability of workflow systems in real industrial and commercial operations. This paper deals with adaptation management of collaborative workflow changes in such consortia and proposes architecture for implementation of these changes through the process of component integration and synchronization where by existing workflow systems adapt to the changes. This paper describes conceptual framework required for prototype implementation resulting in new collaborative workflow adaptation.